A bibliometric analysis of traditional Chinese non-pharmacological therapies in the treatment of knee osteoarthritis from 2012 to 2022 - Zhang, Shouyao; Wang, Yuanwang; Zhou, Meng; Jia, Shan; Liu, Ye; Zhang, Xinghe; Tai, Xiantao (Frontiers in Neuroscience, 2023)
Objective The benefits of traditional Chinese non-pharmacological therapies in the treatment of Knee osteoarthritis (KOA) are receiving increasing attention. Therefore, this study aims to systematically analyze the global research on the treatment of KOA by Chinese traditional non-pharmacological therapies using bibliometric analysis and present the results with a knowledge map form. Methods Literature related to traditional Chinese non-pharmacological therapies used in the treatment of KOA from 2012 to 2022 was searched from the Web of Science core database and PubMed database. CiteSpace, SCImago Graphica and VOSviewer were used to extract nations, institutions, journals, authors, references, keywords, as well as the most widely used acupoints, therapies and evaluation indexes. Results A total of 375 literature have been included. 32 countries around the world have participated in the research. China, the United States, and Europe were at the center of the global cooperation network. The most prolific institutions and authors were from China represented by Cun-zhi Liu and Jian-feng Tu of Beijing University of Chinese Medicine, the institution with the highest cited frequency was University of York, and “Osteoarthritis Cartilage” was the most frequently cited journal. The most frequently cited literature was “OARSI guidelines for the non-surgical management of knee, hip, and poly articular osteoarthritis.” 22 kinds of Chinese non-pharmacological therapies were used to treat KOA, among which acupuncture was the most commonly used one, and ST36 (Zusanli) and WOMAC were the most commonly selected acupoint and evaluation index. Conclusion In the past decade, the value of Chinese non-pharmacological therapies in the treatment of KOA has received widespread attention. It was a common concern of global researchers to relieve the pain of KOA patients and restore the quality of life. Under the background that acupuncture accounts for a relatively high proportion, the next step may consider how to make the balanced development of a variety of Chinese non-pharmacological therapies. In addition, the problem of how to eliminate the placebo effect maybe the direction of future research.